Brain–Behavior Associations for Risk Taking Depend on the Measures Used to Capture Individual Differences - Tisdall, Loreen; Frey, Renato; Horn, Andreas; Ostwald, Dirk; Horvath, Lilla; Pedroni, Andreas; Rieskamp, Jörg; Blankenburg, Felix; Hertwig, Ralph; Mata, Rui (Frontiers in Behavioral Neuroscience, 2020)
Maladaptive risk taking can have severe individual and societal consequences, thus individual differences are prominent targets for intervention and prevention. Although brain activation has been shown to be associated with individual differences in risk taking, the directionality of the reported brain-behavior associations is less clear. Here we argue that one aspect contributing to the mixed results is low convergence between risk-taking measures, especially between the behavioral tasks used to elicit neural functional markers. To address this question, we analyzed within-participant neuroimaging data for two widely used risk-taking tasks collected from the imaging subsample of the Basel–Berlin Risk Study (N = 116 young human adults). Focusing on core brain regions implicated in risk taking (nucleus accumbens, anterior insula, and anterior cingulate cortex), for the two tasks we examined group-level activation for risky versus safe choices, as well as associations between local functional markers and various risk-related outcomes, including psychometrically-derived risk preference factors. While we observed common group-level activation in the two tasks (notably increased nucleus accumbens activation), individual differences analyses support the idea that the presence and directionality of associations between brain activation and risk taking varies as a function of the risk-taking measures used to capture individual differences. Our results have methodological implications for the use of brain markers for intervention or prevention.